Born to be criminal the discourse on criminality and the practice of punishment in late imperial Russia and early Soviet Union : interdisciplinary approaches - The born and the common criminal - the discourse on criminality and the practice of punishment in late imperial Russia and early Soviet Union; Nicolosi, Riccardo 1965-; Hartmann, Anne 1954- (Lettre, 2017)
This collection of essays explores the continuities and disruptions in the perceptions of criminality, its causes and ways of fighting it in late imperial Russia and the early Soviet Union. It focuses on both the discourse on criminality and thus the conceptualisation of criminality in various disciplines (criminology, psychiatry, and literature), and penal practice, that is, different aspects of criminal law and anti-crime policy. Thus, the volume is markedly interdisciplinary, with authors representing a variety of approaches in history and literary studies, from social history to discourse analysis, from the history of sciences to text analysis.